Identification of Dandelion Taraxacum officinale Leaves Components and Study Its Extracts Effect on Different Microorganisms - Jassim, Abdul Kadir M N; Farhan, Safanah Ahmed; Noori, Omar Mohammed (Al-Nahrain Journal of Science, 2012)
Natural plant Dandelion Taraxacum officinale have been used as a phytomedicine, in this study, the chemical components of the Dandelion Taraxacum officinale leaves in watery and alcoholic extracts were identified. The results showed that watery extract was alkaline (presence of alkaloids) while the alcoholic extract was acidic in these contained: glycosides, alkaloids, phenolic compounds, tannins, flavonoids and proteins, while the saponins and resins were not found. The result also showed that high concentrations of the following trace elements were found in the leaves (K ,Ca , Na ,Fe) with 185.1, 22, 19.5, 11.2 ppm, respectively and low concentrations of (Zn, Cd, Cu) with 6.3, 1.3, 0.2 ppm, respectively. The effect of these extracts on the different microorganisms were studied. It has been found that the concentration 0.5 mg/ml was effective on the inhibition of the growth of the intended bacteria (for both extracts) especially Gram positive, Staphylococcus aureus and the alcoholic extracts with concentration 0.5 mg/ml was more effective on the Gram negative, E.coli, than the watery extract, while less than 0.1 mg/ml failed to inhibit any microorganisms. The High Performance Liquid Chromatography (HPLC) was used to identify some flavonoids as compared to standard one; the analysis showed that both kaempferol and morin were absent.